Zeitgeist publication: a storytelling project with residents and design students. Issue 1 (2nd January 2019) - Hannan, Jon; Raber, Caylee; Ellis, Emily; Beyzaei, Nadia; Levi, Donna; Phinney, Alison; Sakamoto, Mariko
Abstract: In Spring 2018 and then again in Fall 2018, residents in a long-term care facility came together with undergraduate communication design students, to co-design and co-write a mini publication series featuring resident stories. Through our project, small teams of two to three students were paired with two to three residents, to create a mini-publication over the course of six visits with each other. The purpose of the Zeitgeist project was to create a platform for meaningful exchange and social interaction between students, residents, their families and care home staff through both the design process and the final design outcomes. This project gives voice to residents, providing an opportunity for creative and emotional expression, stimulation of positive memories and the engagement of residents in a unique and meaningful activity. Simultaneously this project offers design students learning opportunities in storytelling, publication design, co-design and participatory design research. This project was inspired by the Zeitgeist Kollektiv, a public editorial design and storytelling project within a care home system.